Preparation method of lithium manganese iron phosphate positive electrode material
The carbon-coated lithium manganese iron phosphate cathode material was prepared by hydrothermal and high-temperature sintering methods, which solved the shortcomings of existing materials in terms of energy density and electrochemical properties, and achieved higher conductivity and cycling stability.
Patent Information
- Application Number
- CN202411791058.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-04-11
AI Technical Summary
The existing lithium iron phosphate (LiFePO4) and lithium manganese phosphate (LiMnPO4) cathode materials have shortcomings in energy density and electrochemical properties, especially LiMnPO4 has slow reaction kinetics, poor electron and ion conductivity, and manganese dissolution problems.
The specific steps include dissolving manganese iron phosphate lithium ferrous phosphate in deionized water, adding phosphoric acid and ammonia water to form a phosphorus salt solution, then adding hydrogen peroxide and phosphorus salt solution dropwise, controlling the pH value of the reaction solution, carrying out hydrothermal reaction and high temperature sintering, and finally obtaining carbon-coated LiMnxFe1-xPO4@C material.
This method can improve the electrochemical performance of lithium manganese iron phosphate positive electrode material, enhance its conductivity and cyclic stability, and significantly improve the energy density and electrochemical performance of the material.
Smart Images

Figure CN119797307A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of lithium ion battery positive electrode materials, and specifically relates to a method for preparing lithium manganese iron phosphate positive electrode material. Background Art
[0002] Phosphate-based cathode materials are considered as potential alternatives to commercial layered materials due to their excellent structural stability, high safety and outstanding cost advantages. Among them, olivine-structured lithium iron phosphate (LiFePO4) has been widely studied due to its high theoretical capacity, good safety characteristics, high thermochemical stability and low cost. However, compared with other commercial cathode materials LiCoO2 (~4.0 V) and LiMn2O4 (~4.0 V), LiFePO4 has a relatively low redox potential (~3.4 Vvs. Li + / Li), which results in low energy density, which limits its application in the market to a certain extent. LiMnPO4, which also has an olivine structure, is obviously more attractive than LiFePO4 because of its redox potential of up to ~4.1 V. However, LiMnPO4 has many problems such as slow reaction kinetics, poor electronic and ionic conductivity, and Jahn-Teller effect during the chemical reaction leading to manganese dissolution. In previous research work, the electronic conductive layer and particle nano-size control methods have been used to shorten the Li + In addition, another effective strategy is to form a solid solution phase with an olivine structure, such as LiMn x Fe 1-x PO4 solid solution, in which Fe partially replaces Mn, can increase the LiMn x Fe 1-x The solubility limit of PO4 can reduce the miscibility gap between the charge and discharge phases, thereby improving the electrochemical performance of the material. x Fe 1-x PO4 not only has the high safety performance and long cycle performance of LiFePO4, but also has a high redox potential of ~4.1 V. x Fe 1-x PO4 has a theoretical specific capacity comparable to that of LiFePO4, which also indicates that under the same conditions, LiMn x Fe 1-x PO4 material will show higher energy density than LiFePO4. While having many advantages, LiMn x Fe 1-xPO4 also has some problems. It has worse conductivity than LiFePO4, and also has the problem of poor cycle performance caused by manganese ion dissolution. In addition, it is easy to cause non-uniform solid solution during the synthesis process, resulting in poor electrochemical performance of the material. It is usually optimized by surface carbon coating, nano-processing and high-valent metal ion doping. Summary of the invention
[0003] The raw materials used in the present invention are ferrous sulfate, manganese chloride, PVP, hydrogen peroxide, phosphoric acid, ammonia water, carbon source, and manganese tetraoxide. The specific preparation process is: add manganese chloride and ferrous sulfate to deionized water in turn, stir and dissolve, and obtain a manganese-iron mixed solution; Subsequently, phosphoric acid and ammonia water are prepared into a phosphate solution, and a mixed solution of the phosphate solution and hydrogen peroxide is added dropwise to the manganese-iron mixed solution, and reacted for a certain time after the addition is completed, and then ammonia water is added dropwise to maintain the pH of the reaction solution to fluctuate within a certain range. After the reaction is completed, centrifugal washing is performed to obtain precursor A; Then, the precursor A after centrifugal washing is re-slurried with water, hydrogen peroxide and PVP are added to the slurry and stirring is continued for 30-60 minutes, and the mixed slurry and phosphoric acid are added to a high-pressure reactor for hydrothermal reaction at 120-200° C. for 6-10 hours to obtain a ferromanganese phosphate precursor material; Then, the ferromanganese phosphate precursor material, lithium source and carbon source are added to the solvent anhydrous ethanol and placed in a ball mill for 4-10 hours at a ball milling speed of 200-800 r / min. Then, the ball-milled and dried material is transferred to a tube furnace and sintered at 400-800℃ for 8-14 hours under a nitrogen atmosphere to finally obtain lithium ferromanganese phosphate material.
[0004] The molar ratio of ferrous sulfate to manganese chloride is 0.1-10.
[0005] The phosphate salt solution is a phosphate salt solution prepared by phosphoric acid and ammonia water with a pH value of 6.5-7.5; The molar ratio of phosphate salt to hydrogen peroxide is 3-1:1, the content of phosphate salt is 8.0-8.5wt%, and the pH is adjusted to 2.0-3.0, and the aging reaction is carried out for 20-50 minutes; During the co-precipitation synthesis process, an amorphous manganese-iron compound is generated, which facilitates more uniform solid solution of manganese-iron in the subsequent hydrothermal process and improves the electrochemical performance of lithium manganese-iron phosphate using manganese-iron phosphate as a precursor.
[0006] Ammonia water was added to the reaction solution to adjust the pH to 8.5-10.0.
[0007] The molar ratio of hydrogen peroxide to metal ions is 1-1:3, the concentration of hydrogen peroxide is 22.0-22.3wt%, the amount of PVP added is 1-10% of the mass of the ferromanganese mixed solution; the molar ratio of phosphoric acid to manganese source is 1-2:1.
[0008] The lithium source includes one or more of lithium hydroxide, lithium carbonate and lithium acetate; The carbon source includes one or more of asphalt, graphene, carbon nanotubes, expandable graphite, natural graphite, artificial graphite and hard carbon.
[0009] Another technical solution of the present invention is to provide a positive electrode material for a lithium-ion battery, and the positive electrode material for a lithium-ion battery is prepared by using the method described to prepare a lithium iron manganese phosphate positive electrode material.
[0010] The preparation method of a lithium manganese iron phosphate positive electrode material invented in this patent has the following characteristics: (1) The cost of raw materials is low, and manganese and iron sources are abundant.
[0011] (2) The hydrothermal and high-temperature sintering methods are used to make the synthetic material more uniform.
[0012] (3) Lithium manganese iron phosphate can be synthesized in large quantities, and the experimental scale-up effect is excellent.
[0013] (4) The electrochemical performance of carbon-coated lithium manganese iron phosphate material is significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 This is a comparison chart of the XRD of the sample prepared in Example 1 and the standard card.
[0015] Figure 2 The charge and discharge curves of the sample prepared in Example 1 at 0.1, 0.3, and 0.5 C.
[0016] Figure 3 This is a comparison chart of the XRD of the ferromanganese phosphate prepared in Example 1 and the standard card. DETAILED DESCRIPTION
[0017] Example 1 38.93 g of ferrous sulfate and 48.40 g of manganese chloride were added to 600 mL of deionized water to obtain a manganese-iron mixed solution; ammonia water and phosphoric acid were prepared into a phosphate solution with a pH of 7.1, and then 93.57 g of phosphate was added to 18.53 g of hydrogen peroxide and stirred and mixed evenly, and then added dropwise to the manganese-iron mixed solution, and the pH of the reaction system was monitored between 2.1 and 2.3, and the reaction was aged for 30 minutes, and then ammonia water was added dropwise to the reaction system, and the pH of the reaction system was adjusted to 8.5-10.0 and aged again for 30 minutes, and then 3 g of PVP and 4.5 g of hydrogen peroxide were successively added to the above mixed solution and stirred and mixed for 30 minutes, and then the mixed solution and 63.18 g of phosphoric acid were added to the lining of the reactor and then transferred to a hydrothermal oven for hydrothermal reaction at 160 ° C for 6 hours. Then it was filtered and dried at 80 ° C in a constant temperature drying oven for 8 hours to obtain precursor material A. 55.22 g of precursor A, 21.01 g of lithium carbonate, and 10.2 g of glucose were successively added to a ball mill containing 300 mL of anhydrous ethanol and ball milled at a speed of 600 r / min for 10 h. The mixture was taken out and dried at 80 °C for 4 h, then transferred to a tubular resistance furnace and heated to 650 °C at a heating rate of 5 °C / min for 12 h to obtain carbon-coated LiMn 0.6 Fe 0.4 PO4@C material. Figure 1 LiMn 0.6 Fe 0.4 The XRD comparison of PO4@C and the standard card corresponds well to the LiMnPO4 standard card (PDF#74-0375). It can be clearly observed that the characteristic peak shifts to the right, showing good crystallinity. Figure 2 LiMn 0.6 Fe 0.4 The charge-discharge curves of PO4@C at 0.1, 0.3, and 0.5 C, respectively. At 0.1, 0.3, and 0.5 C, it can contribute 148.7, 146.2, and 145.5 mAh g -1 The discharge specific capacity shows very excellent electrochemical performance. Figure 3 This is the XRD comparison chart of precursor A with the standard card, which has good crystallinity and no obvious impurity peaks are observed.
[0018] Example 2 48.66 g of ferrous sulfate and 40.33 g of manganese chloride were added to 600 mL of deionized water to obtain a manganese-iron mixed solution. Ammonia water and phosphoric acid were prepared into a phosphate solution with a pH of 7.1. Then 93.57 g of phosphate was added to 18.53 g of hydrogen peroxide and stirred and mixed evenly, and then added dropwise to the manganese-iron mixed solution. The pH of the reaction system was monitored between 2.1 and 2.3. The reaction was aged for 30 minutes. Then ammonia water was added dropwise to the reaction system to adjust the pH of the reaction system to 8.5-10.0 and then aged for 30 minutes. Then 3 g of PVP and 3.7 g of hydrogen peroxide were successively added to the above mixed solution and stirred and mixed for 30 minutes. Then the mixed solution and 57.24 g of phosphoric acid were added to the lining of the reactor and then transferred to a hydrothermal oven for hydrothermal reaction at 160 ° C for 6 h. Then it was filtered and dried at 80 ° C in a constant temperature drying oven for 8 h to obtain precursor material B. 55.22 g of precursor B, 21.01 g of lithium carbonate, and 10.2 g of glucose were successively added to a ball mill containing 300 mL of anhydrous ethanol and ball milled at a speed of 600 r / min for 10 h. The mixture was taken out and dried at 80 °C for 4 h, then transferred to a tubular resistance furnace and heated to 650 °C at a heating rate of 5 °C / min for 12 h to obtain carbon-coated LiMn 0.5 Fe 0.5 PO4@C material.
[0019] Example 3 29.20 g of ferrous sulfate and 56.47 g of manganese chloride were added to 600 mL of deionized water to obtain a manganese-iron mixed solution. Ammonia water and phosphoric acid were prepared into a phosphate solution with a pH of 7.1. Then 93.57 g of phosphate was added to 18.53 g of hydrogen peroxide and stirred and mixed evenly, and then added dropwise to the manganese-iron mixed solution. The pH of the reaction system was monitored between 2.1 and 2.3. The reaction was aged for 30 minutes. Then ammonia water was added dropwise to the reaction system to adjust the pH of the reaction system to 8.5-10.0 and then aged for 30 minutes. Then 3 g of PVP and 7.2 g of hydrogen peroxide were successively added to the above mixed solution and stirred and mixed for 30 minutes. Then the mixed solution and 65.97 g of phosphoric acid were added to the lining of the reactor and then transferred to a hydrothermal oven for hydrothermal reaction at 160 ° C for 6 h. Then it was filtered and dried at 80 ° C in a constant temperature drying oven for 8 h to obtain precursor material C. 55.22 g of precursor C, 21.01 g of lithium carbonate, and 10.2 g of glucose were successively added to a ball mill containing 300 mL of anhydrous ethanol and ball milled at a speed of 600 r / min for 10 h. The mixture was taken out and dried at 80 °C for 4 h, then transferred to a tubular resistance furnace and heated to 650 °C at a heating rate of 5 °C / min for 12 h to obtain carbon-coated LiMn 0.7 Fe0.3 PO4@C material.
[0020] Comparative Example 1 38.93 g of ferrous sulfate and 48.40 g of manganese chloride were added to 600 mL of deionized water to obtain a manganese-iron mixed solution. Ammonia water and phosphoric acid were prepared into a phosphate solution with a pH of 7.1, and then 93.57 g of phosphate was added dropwise to the manganese-iron mixed solution. The pH of the reaction system was monitored between 2.1 and 2.3, and the reaction was aged for 30 minutes. Ammonia water was then added dropwise to the reaction system to adjust the pH of the reaction system to 8.5-10.0 and aged again for 30 minutes. Then 3 g of PVP and 4.5 g of hydrogen peroxide were added to the above mixed solution and stirred for 30 minutes. Then the mixed solution and 63.18 g of phosphoric acid were added to the lining of the reactor and then transferred to a hydrothermal oven for hydrothermal reaction at 160 ° C for 6 hours. Then it was filtered and dried at 80 ° C in a constant temperature drying oven for 8 hours to obtain precursor material D. 55.22 g of precursor D, 21.01 g of lithium carbonate, and 10.2 g of glucose were successively added to a ball mill containing 300 mL of anhydrous ethanol and ball milled at a speed of 600 r / min for 10 h. The mixture was taken out and dried at 80 °C for 4 h, then transferred to a tubular resistance furnace and heated to 650 °C at a heating rate of 5 °C / min for 12 h to obtain carbon-coated LiMn 0.6 Fe 0.4 PO4@C-1 material.
[0021] Comparative Example 2 22.18 g of ferric phosphate and 50.41 g of manganese tetraoxide were added to 600 mL of deionized water and stirred evenly to obtain a manganese-iron mixed solution. Subsequently, 3 g of PVP and 4.5 g of hydrogen peroxide were successively added to the above mixed solution and stirred for 30 min. Then, the mixed solution and 63.18 g of phosphoric acid were added to the lining of the reactor and then transferred to a hydrothermal oven for hydrothermal reaction at 160 ° C for 6 h. Then, it was filtered and dried at 80 ° C in a constant temperature drying oven for 8 h to obtain the precursor material E. 55.22 g of precursor E, 21.01 g of lithium carbonate, and 10.2 g of glucose were successively added to a ball mill containing 300 mL of anhydrous ethanol, and the ball mill was mixed at a speed of 600 r / min for 10 h. After the mixture was taken out and dried at 80 ° C for 4 h, it was transferred to a tubular resistance furnace and heated to 650 ° C at a heating rate of 5 ° C / min for 12 h to obtain carbon-coated LiMn 0.6 Fe 0.4 PO4@C-2 material.
[0022] Comparative Example 3 38.93 g of ferrous sulfate and 48.40 g of manganese chloride were added to 600 mL of deionized water to obtain a manganese-iron mixed solution. Ammonia water and phosphoric acid were prepared into a phosphate solution with a pH of 7.1, and then 93.57 g of phosphate was added dropwise to the manganese-iron mixed solution. The pH of the reaction system was monitored between 2.1 and 2.3, and the reaction was aged for 30 minutes. Ammonia water was then added dropwise to the reaction system to adjust the pH of the reaction system to 8.5-10.0 and aged again for 30 minutes. Then 3 g of PVP and 4.5 g of hydrogen peroxide were successively added to the above mixed solution and stirred for 30 minutes. Then the mixed solution and 63.18 g of phosphoric acid were added to the lining of the reactor and then transferred to a hydrothermal oven for hydrothermal reaction at 160 ° C for 6 hours. Then it was filtered and dried at 80 ° C in a constant temperature drying oven for 8 hours to obtain the precursor material F. 55.22 g of precursor F, 21.01 g of lithium carbonate, and 10.2 g of glucose were successively added to a ball mill containing 300 mL of anhydrous ethanol and ball milled at a speed of 600 r / min for 10 h. The mixture was taken out and dried at 80 °C for 4 h, then transferred to a tubular resistance furnace and heated to 650 °C at a heating rate of 5 °C / min for 12 h to obtain carbon-coated LiMn 0.6 Fe 0.4 PO4@C-3 material.
[0023] Table 1 Summary of electrical performance results of various embodiments and comparative examples .
Claims
1. A method for preparing a lithium manganese iron phosphate positive electrode material, characterized in that: The steps include: (1) Add a certain proportion of manganese chloride and ferrous sulfate into water successively and stir to dissolve to obtain a manganese-iron mixed solution; (2) preparing a mixed solution of a phosphate solution and hydrogen peroxide in a certain proportion and adding the mixed solution dropwise to the manganese iron mixed solution. After the addition is completed, aging reaction is carried out for a certain period of time. Then, ammonia water is added dropwise to the reaction solution to maintain the pH value of the reaction solution within a certain range. After the reaction is completed, centrifugal washing is performed to obtain precursor A. (3) Re-slurrying the precursor A with water, adding a certain amount of hydrogen peroxide and PVP to the slurry and continuing to stir evenly, adding the evenly mixed slurry and phosphoric acid into a high-pressure reactor to carry out a hydrothermal reaction, and drying the product after the hydrothermal reaction to obtain ferromanganese phosphate powder; (4) mixing the ferromanganese phosphate powder with the lithium source and the carbon source, adding a solvent, and performing ball milling to mix; (5) The ball-milled and dried powder is calcined in an inert atmosphere to obtain a carbon-coated lithium manganese iron phosphate material.
2. The method for preparing the lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: In step (1), the molar ratio of ferrous sulfate to manganese chloride is 0.1-10.
3. The method for preparing the lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The phosphate solution in step (2) is a phosphate solution prepared by phosphoric acid and ammonia water with a pH of 6.5-7.5; The molar ratio of phosphate salt to hydrogen peroxide is 3-1:1, the content of phosphate salt is 8.0-8.5wt%, and the pH is adjusted to 2.0-3.0, and the aging reaction is carried out for 20-50 minutes; Ammonia water was added to the reaction solution to adjust the pH to 8.5-10.
0.
4. The method for preparing the lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: In step (3), the molar ratio of hydrogen peroxide to metal ions is 1-1:3, the concentration of hydrogen peroxide is 22.0-22.3wt%, the amount of PVP added is 1-10% of the mass of the manganese-iron mixed solution; and the molar ratio of the amount of phosphoric acid added to the amount of manganese source added is 1-2:
1.
5. The method for preparing the lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: In step (3), the hydrothermal temperature is 120-200°C and the insulation time is 6-12 h.
6. The method for preparing the lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: In step (4), the lithium source includes one or more of lithium hydroxide, lithium carbonate, and lithium acetate; The carbon source includes one or more of asphalt, graphene, carbon nanotubes, expandable graphite, natural graphite, artificial graphite and hard carbon.
7. The method for preparing lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The ball milling process is performed at 200-800 r / min for 6-8 hours.
8. The method for preparing lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: The high temperature sintering process parameters are: reaction temperature 400-800°C; reaction time 3-48 hours, preferably 8-14 hours; The high temperature sintering process is carried out in any protective gas of nitrogen, hydrogen and argon.
9. A positive electrode material for a lithium ion battery, characterized in that: The lithium manganese iron phosphate positive electrode material is prepared by the method described in any one of claims 1 to 8.
Citation Information
Cited By
Preparation method of ferromanganese phosphate precursor and preparation method of lithium ferromanganese phosphate positive electrode material
CN121717351A